Ways of Forming Self-Assessment Competence in Future Educators. - Meyliyeva N.G (Genius Journals, 2023)
The relationship between future teachers' self-perception, self-esteem, self-description, the desire to appear in a certain way in the eyes of people and their sensitivity to their real life related to existing contradictions.
Keywords: pedagogue; modernization